2018
DOI: 10.2495/arc180081
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Circular Solutions and Services for New Buildings and Refurbishments

Abstract: The housing sector is responsible for more than 50% of global resource extraction, about 50% of world energy consumption, 1/3 of water consumption and furthermore generates about 1/3 of all produced waste. A new, circular approach is needed to enable better decision-making on the selection of innovative architectural solutions for all phases of a building's life cycle. The current building sector's business model must be redesigned to include the application of new and improved methods, solutions and innovativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Low awareness is also perceived in emerging countries, such as Vietnam (Ling and Nguyen, 2013). However, in Europe there is awareness of the need of applying CE, and case studies are widely seen in the literature (Adams et al, 2017; Bertino et al, 2019; Maerckx et al, 2019; Nijgh and Veljkovic, 2019; Ünal et al, 2019). Previous case studies enable the identification of real gaps and points of greatest effort for the effective implementation of the CE in regional civil construction.…”
Section: Results and Discussion: Challenges And Opportunities For An ...mentioning
confidence: 99%
“…Low awareness is also perceived in emerging countries, such as Vietnam (Ling and Nguyen, 2013). However, in Europe there is awareness of the need of applying CE, and case studies are widely seen in the literature (Adams et al, 2017; Bertino et al, 2019; Maerckx et al, 2019; Nijgh and Veljkovic, 2019; Ünal et al, 2019). Previous case studies enable the identification of real gaps and points of greatest effort for the effective implementation of the CE in regional civil construction.…”
Section: Results and Discussion: Challenges And Opportunities For An ...mentioning
confidence: 99%
“…Simultaneously, evaluating the existing buildings using a circularity tool is important, as found in the literature review. Bertino, Menconi [67] clearly indicated that the circularity assessment of existing buildings is critical in order to make decisions at the EOL stage. Based on these analyses, a proper plan can be developed and executed for deciding whether the building is to be reused, disassembled, or deconstructed and whether materials are recycled or disposed of [26].…”
Section: Surveys + Expert Forumsmentioning
confidence: 99%
“…The solids are co-digested together with the organic household waste in small biogas plants. The digested matter is converted to compost in a closed-vessel composting unit with in-built odour abatement (Bertino et al 2018).…”
Section: Urban Wastewatermentioning
confidence: 99%